Perilaku Prososial Ditinjau dari Rasa Syukur pada Persaudaraan Muda-Mudi Vihara Borobudur (PMVB) Medan - Sushella Salihin; Achamd Irvan Dwi Putra; Nurmaizar Nilawati Siregar (Universitas Muhammadiyah Jember, 2020)
Prosocial behavior is an effort to improve welfare and harmony in the social life of the community. This study aims to determine the effect of gratitude on prosocial behavior in the Young-Mudi Brotherhood of Borobudur Temple, Medan. This research was conducted on 149 young people who had joined for one year and aged 18-40 years. The hypothesis in this study was that there was a positive relationship between gratitude and prosocial behavior. Hypothesis testing uses the Pearson Product Moment Correlation technique after an assumption test that includes tests of normality and linearity through the help of SPSS 21 for windows. The results of data analysis showed a correlation coefficient of 0.551 (p 0.000). This shows that the gratitude of young people has a positive and significant effect on prosocial behavior.